Impact of COVID -19 On Personal Finance of Gulf Returnees in Kerala - Ansalna MUHAMMED; T G MANOHARAN (Communications of International Proceedings, 2021)
Kerala Gulf migrants are the backbone of the state and their sweat brings development. Due to the COVID-19 pandemic, overall gulf migrant’s financial position was down streamed and urge many to return home. This paper tries to find the impact of COVID-19 on their income, consumption pattern, savings, and investment. 150 Gulf returnees were selected through random sampling from the Ernakulam district. Primary data was collected using a questionnaire. Percentage analysis, Chisquare test for goodness of fit, and correlation were used for data analysis. Findings show a decrease in income and savings of most returnees and they spend largely for accessing health care facilities.
Keywords: Migrants; COVID-19; Pandemic; personal finance impact